Non-Grain Production of Cultivated Land in Hilly and Mountainous Areas at the Village Scale: A Case Study in Le’an Country, China - Zuo Zhang; Lin Zheng; Dajie Yu (Land, 2023)
Non-grain production of cultivated land (NGPCL) is an essential factor that affects food security and sustainable agricultural development. Due to the large population and limited land area present in China, cultivated land resources are more extensive and valuable in hilly and mountainous areas, though the expansion of NGPCL threatens food security and is detrimental to the sustainable use of cultivated land resources. To better understand the problem of NGPCL in hilly and mountainous areas, this paper initially classifies NGPCL into four distinct types, namely unplanted cultivated land (UCL), planted non-grain crops (PNGC), engineering recoverable (ENR), and immediately recoverable (IMR), based on their planting types and attributes. Subsequently, we analyzed the spatial patterns and differentiation characteristics of these NGPCL types in Le’an County at the village scale through exploratory spatial data analysis and studied their driving factors using the geographical detector model. The findings show that the NGPCL rate in Le’an County was 18.53%, with ENR occupying the largest area, followed by PNGC and UCL, while IMR had the smallest area. The spatial distribution of NGPCL in Le’an County suggests that there are correlations with all four types of NGPCL, which exhibit spatial clustering, except for IMR, which displays spatial heterogeneity. We attribute the phenomenon of NGPCL in Le’an County to natural, social, and economic factors, with the driving forces having varying degrees of influence. Specifically, slope, altitude, and cultivated land protection intensity play significant roles in the overall NGPCL. This paper is of crucial significance to the local agricultural management department’s efforts to prevent and control the non-grain production of cultivated land and the Chinese Government’s efforts to ensure food security.